Perilaku mahasiswi Fakultas Kedokteran Universitas Sam Ratulangi dalam pencegahan kekerasan terhadap perempuan di Manado - Tjia, Laura; Palandeng, Henry M. F.; Siagian, Iyone T. S. (UNIVERSITAS SAM RATULANGI, 2016)
Objective: To describe the behavior of the female students of the medical Faculty of Sam Ratulangi University (UNSRAT) against the violence . Methods: This research used the descriptive qualitative method with two focus group discussion (FGD) consisted of 13 people with six people for formal interview. Results: This research shows that the student has an excellent knowledge against women violations and a good attitude against them. Conclusion: The most effective ways to deal with these violence according to this result is by educating the society. Keywords: behavior, student, prevention, violence